A new single‐phase multilevel converter topology with reduced power electronic devices, voltage rating on switches, and power losses. (30th April 2018) - Alishah, Rasoul Shalchi; Hosseini, Seyed Hossein; Babaei, Ebrahim; Sabahi, Mehran
Summary: In this paper, a new extended single‐phase structure for multilevel converter is presented which consists of several bidirectional and unidirectional switches along with dc voltage sources. To generate all possible levels at output voltage waveform, 2 methods are presented for determination of the amplitudes of dc voltage sources. The proposed structure is compared with traditional cascade H‐bridge multilevel converter and other recently proposed structures in terms of the number of power electronic components, voltage rating on switches, and power losses. Based on the comparison results, it is demonstrated that the proposed structure needs minimum number of IGBTs, gate drivers, and anti‐parallel diodes. Moreover, the voltage rating on bidirectional and unidirectional switches in the proposed structure is less than other similar topologies. Also, power losses analysis on the proposed topology is investigated. It is shown that the power loss of proposed topology is less than H‐bridge multilevel converter topology. The number of on‐state switches in the current path of proposed topology is much lower than other topologies which lead to the reduction of voltage drop on the switches and power losses. Both experimental and simulation works are provided to verify the performance of the presented structure. Abstract : In this paper, a new extended single‐phase structure for multilevel converter is presented which consists of several bidirectional and unidirectional switches along with dc voltage sources. Based on the comparison results, it is demonstrated that the proposed structure needs minimum number of IGBTs, gate drivers, anti‐parallel diodes, voltage rating on switches, and power losses. Both experimental and simulation works are provided to verify the performance of the presented structure.